Studi Komunitas Nekton Di Kawasan Konservasi Kura-Kura Universitas Bengkulu Dan Pengembangan Pembelajaran Berbasis Lingkungan - Desi Enersy; Bhakti Karyadi; Endang Widi Winarni (PendIPA Journal of Science Education, 2017)
This study aims to inventory the type of necton, knowing the structure of the necton community and measuring the critical thinking skills of students of class VII.1 SMPN 1 Ujan Mas Kepahiang. The results showed that the necton obtained from the Taman Pintar pond amounted to 7 species and Pipi Putih Pond totaling 4 species. The necton species in the Taman Pintar pond  with the highest KP, KS, and FK values are tin head fish with KP, KR, and FK values respectively  0.102 idv / m2, 75.71% and 83%. While on the Pipi Putih Pond is local catfish species with the value of KP, KR, FK of 0.01 idv / m2, 39.29% and 25%. Then dominance index (H ') in the Taman Pintar pond is 0.61 and C' Pipi Putih pond  = 0.76. While the index of diversity of necton species in both ponds also belonged to very low category with H’ value of Taman Pintar Pond = 0.28 and H' of Pipi Putih pond  = 0.17. The result of Percentage Of Agreement test showed that  environment-based learning tools developed are included in the category highly feasible to be tested. Students’ critical thinking ability on the perpormance aspect shows 33 ,3 % percentage including critically critical criteria and 66,7 % including critical criteria. While Students’ critical thinking ability on the cognitive aspect shows four criteria, that are very critical as 26 %, crittical criteria 40 %, criteria critical enough 27 % and  criteria less 7 %